Rancang Bangun Sistem Informasi Kepegawaian pada PT Sukses Wahana Maritim - Dimas P, Krispinus Pierre; Mulyati, Mulyati (MDP Student Conference, 2024)
In the current digital era, Information Systems are widely utilized in various fields, such as human resources management. PT Sukses Wahana Maritim is a shipping company located in the city of Palembang. The research employs the Iterative method. The company faces a challenge with its non-integrated human resources system, leading to ineffective performance within the organization. The aim of this research is to design and construct an efficient and integrated human resources information system at PT Sukses Wahana Maritim. The focus of the study is on developing a system capable of effectively managing human resources to enhance operational efficiency within the company. The implementation of this information system will enable PT Sukses Wahana Maritim to obtain information regarding attendance, employee data, mutations, layoffs, and employee recruitment.